2021
DOI: 10.52442/rjhs.v2i2.63
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients with heart failure in tertiary care hospitals of Peshawar, KP, Pakistan; a cross-sectional study

Abstract: Introduction: Quality of life is a multifaceted concept which reflect a number of parameters including different symptoms. These factors are affected by many factors including age, gender, marital status, education levels and socioeconomic status. Quality of life in majority of patients with different medical conditions is significantly affected, however, little is known in patients with heart failure coming to tertiary care hospitals of Peshawar. This study was designed to assess quality of life among heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Nearly all couples were Consanguineous (96.7%). The current percentage was higher than previously reports, Tayebi N et al [26] reported that cousin marriage was reported in 25% of participant, other study shows that 68% of participant were consanguineous [ 27], another study reported that 75.5% were consanguineous and 82.3% of those with consanguineous marriage were from rural area [28]. The high incidence of consanguineous marriage is ascribed to societal practices that involve planned marriages within families and general public ignorance of the negative implications of such a practice.…”
Section: Discussioncontrasting
confidence: 62%
“…Nearly all couples were Consanguineous (96.7%). The current percentage was higher than previously reports, Tayebi N et al [26] reported that cousin marriage was reported in 25% of participant, other study shows that 68% of participant were consanguineous [ 27], another study reported that 75.5% were consanguineous and 82.3% of those with consanguineous marriage were from rural area [28]. The high incidence of consanguineous marriage is ascribed to societal practices that involve planned marriages within families and general public ignorance of the negative implications of such a practice.…”
Section: Discussioncontrasting
confidence: 62%